Intrinsic Charge Transport across Phase Transitions in Hybrid Organo‐Inorganic Perovskites. Issue 30 (17th May 2016) - Yi, Hee Taek; Wu, Xiaoxi; Zhu, Xiaoyang; Podzorov, Vitaly
Abstract : Hall effect measurements in CH3 NH3 PbBr3 single crystals reveal that the charge‐carrier mobility follows an inverse‐temperature power‐law dependence, μ ∝ T − γ, with the power exponent γ = 1.4 ± 0.1 in the cubic phase, indicating an acoustic‐phonon‐dominated carrier scattering, and γ = 0.5 ± 0.1 in the tetragonal phase, suggesting another dominant mechanism, such as a piezoelectric or space‐charge scattering.